Contagious keratoconjuctivitis in goats due to Branhamella (Moraxella) ovis - BOURDZI-HATZOPOULOU (ΜΠΟΥΡΤΖΗ-ΧΑΤΖΟΠΟΥΛΟΥ Ε.) E.; TSAKNAKIS (Η. ΤΣΑΚΝΑΚΗΣ) I.; PETRIDOU (Ε. ΠΕΤΡΙΔΟΥ) E. (Journal of the Hellenic Veterinary Medical Society, 2018)
Incidents of contagious kerato conjuctivitis in two flocks of goats in Chalkidiki Prefecture are described. The disease was only observed in young animals approximately two years of age. The early signs were excessive lacrimation, photophobia and blepharospasm, while the bright sunlight was revealed irritating for the affected eyes. Conjunctivitis and mucopurulent secretion was also observed at the late stage of the disease. Many animals with keratitis end up totally blind. The infection of the eyes was either lateral of bilateral. Branhamella ovis was isolated in almost pure culture, from lacrimal secretion in a large number of samples (32/35). The identification was based on the organism’s morphology, cultural behaviour and biochemical reactions. The microbiological examination of the samples revealed only one kind of isolate. No other organisms that could cause similar clinical findings were isolated. Therefore, it was assumed that the etiological agent of the described cases was B.ovis. It is possible that certain environmental agents such as dust, flies or bright sunlight, that were present at that time of the year because of the prolonged summer, acted as predisposing factors. Although the disease exists in our country for years, it is the first time that the pathogen agent has been isolated and identified. A successful treatment was performed at the early stage of the disease by the topical application of antibiotics.